Aberrant Level of Skp2 and p27KIP1 in Intraductal Proliferative Lesions is Associated with Tumorigenesis. (3rd July 2017) - Lv, Yan; Niu, Yun; Li, Chong; Zheng, Xu; Geng, Qiang; Han, Yanyan
ABSTRACT: Breast cancer is one of the leading causes of cancer-related death in women worldwide. Here we aimed to examine the expression status of S-phase kinase-associated protein 2 (Skp2) and p27 KIP1, and assess the significance of Skp2 plus p27 KIP1 expression in patients with intraductal proliferative lesions, including ductal carcinoma in situ (DCIS) and atypical ductal hyperplasia (ADH). Skp2 and p27 KIP1 mRNA levels in DCIS, ADH, flat epithelial atypia, and usual ductal hyperplasia (UDH) were evaluated by quantitative real-time reverse transcription polymerase chain reaction and protein expression was evaluated immunohistochemically in 60 fresh tissues and 120 paraffin-embedded tissues from patients with the four subtypes above. We found that the protein and mRNA level of Skp2 were significantly increased in DCIS and ADH as compared with that in UDH. In contrast, p27 KIP1 protein and mRNA levels were reduced. Based on the above findings, abnormal levels of Skp2 and p27 KIP1 have probably been involved in the pathogenesis of ADH and DCIS. Thus, Skp2 and p27 KIP1 may serve as important diagnosis markers.